Preparation of Preformed Iodixanol Gradients - John Graham (The Scientific World Journal)
The Protocol Article describes the strategies for the formation of preformed discontinuous and continuous density gradients. Most of the techniques can be applied to the use of any gradient solute but some of the detailed recommendations on continuous gradients only apply to iodixanol gradients because of variations in viscosity and rates of diffusion between different solute types. Operational variations that require consideration when dealing with specific types of biological particle are also dealt with at the end of this Protocol Article.